Thermoplastic resin composition

JP7636188B2Active Publication Date: 2025-02-26ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021016884
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-10
Filing Date
2021-02-04
Publication Date
2025-02-26
Estimated Expiration
2041-02-04

AI Technical Summary

Benefits of technology

【0009】 本発明の熱可塑性樹脂組成物は、高い透過率と同時に低いヘイズを示し、透明性に優れ、耐傷付性、靭性にも優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636188000001
    Figure 0007636188000001
  • Figure 0007636188000002
    Figure 0007636188000002
  • Figure 0007636188000003
    Figure 0007636188000003
Patent Text Reader

Abstract

To provide a thermoplastic resin composition which exhibits high transmittance and low haze, and is excellent in transparency, scratch resistance and toughness.SOLUTION: A thermoplastic resin composition contains: 50-99 mass% of a methacrylic resin (A) which is composed of 80.0-99.9 mass% of a methacrylate monomer unit, 0.1-20.0 mass% of a vinyl monomer unit composed of a vinyl monomer copolymerizable with the methacrylate monomer unit excluding a maleic acid and a maleic acid anhydride and 0-4.0 mass% of a maleic acid and / or a maleic acid anhydride monomer unit; and 1-50 mass% of thermoplastic polyurethane (B) having a polyester polyol-derived structural unit and an isocyanate-derived structural unit having an alicyclic group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition. [Background technology]

[0002] Methacrylic resins are characterized by having higher light transmittance, weather resistance, and rigidity as transparent resins than other plastic transparent resins, and have been used in a wide range of applications such as vehicle parts, lighting fixtures, building materials, signs, nameplates, paintings, and display device windows. Among them, methacrylic resin compositions are widely used as design parts for home appliances and office automation products and interior and exterior design parts for automobiles due to their excellent appearance. However, methacrylic resin compositions have the problem of low toughness and that the surface is scratched when used outdoors, and therefore their use is often restricted in molded articles with mechanical parts, applications where they are used in a distorted state, and outdoor use.

[0003] In Patent Document 1, a method of using a multi-layer (meth)acrylic rubber polymer is attempted to improve toughness. However, these compositions cause stress whitening. Stress whitening is haze that occurs when subjected to bending stress. Furthermore, scratch resistance has not been improved in these compositions, and remains a problem.

[0004] As another approach to improving toughness, Patent Document 2 considers compounding with elastomers and describes a transparent low-temperature impact-resistant plastic mixture consisting of a thermoplastic (TPU) and impact-improved poly(meth)acrylate. According to Patent Document 2, these plastic mixtures exhibit acceptable transparency as well as good impact resistance, high tensile modulus, and good weatherability. The plastic mixture uses a thermoplastic polyurethane having an aliphatic bond. Patent Document 2 shows that a transmittance of 83% is achieved with a mixture of impact-improved poly(meth)acrylate and impact-improved thermoplastic polyurethane having an aliphatic bond under the described test conditions, but a total light transmittance of 83% is insufficient for a transparent material. In addition, the transparency of a material is affected not only by the total light transmittance but also by the haze.

[0005] Patent Document 3 discloses a composition that uses an aliphatic isocyanate having a specific structure and exhibits high transmittance and low haze at the same time, particularly low haze and high transparency, in order to improve the insufficient transparency. However, the haze of the composition disclosed in Patent Document 3 is not sufficiently low, and there is room for improvement in order to use the composition as a transparent material. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2003-183471 A [Patent Document 2] International Publication No. 2007 / 057242 [Patent Document 3] Special Publication No. 2015-532345 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a thermoplastic resin composition which exhibits high transmittance and simultaneously low haze, is excellent in transparency, scratch resistance and toughness. [Means for solving the problem]

[0008] That is, the present invention is as follows. [1] Methacrylic acid Methyl Monomer Unit 93.0~99.5 Mass% and Methyl acrylate and / or ethyl acrylate Monomer Unit 0.5~7.0 mass % and maleic acid and / or maleic anhydride monomer units 0 to 4.0 mass % Methacrylic resin (A) 60~95 % by mass, and a thermoplastic polyurethane (B) having a structural unit derived from a polyester polyol and a structural unit derived from an isocyanate having an alicyclic ring. 5~40 % by mass. [2] The thermoplastic resin composition according to [1], wherein the structural unit derived from an isocyanate having an alicyclic ring has one alicyclic ring. [3] The thermoplastic resin composition according to [1] or [1], wherein the weight average molecular weight of the methacrylic resin (A) is 50,000 to 250,000 as measured by gel permeation column chromatography (GPC). [4] The thermoplastic resin composition according to any one of [1] to [3], wherein the amount of terminal unsaturated double bonds in the methacrylic resin (A) is 0.01 mol % or less. 。 [5] [1] to [3], wherein the mass ratio of structural units derived from an isocyanate having one alicyclic ring is 70 mass% or more relative to the total mass of structural units derived from an isocyanate contained in the thermoplastic polyurethane (B) is 100 mass%. [4] 13. The thermoplastic resin composition according to claim 12 . [6] The thermoplastic resin composition according to any one of [1] to [5], wherein the content of a tertiary amine in 100% by mass of the thermoplastic resin composition is 0.9% by mass or less. [7] The thermoplastic resin composition according to any one of [1] to [6], wherein a total content of the methacrylic resin (A) and the thermoplastic polyurethane (B) is 80 mass% or more relative to 100 mass% of the thermoplastic resin composition, and the thermoplastic resin composition is used for molding. [8] The thermoplastic resin composition according to any one of [1] to [7], wherein the thermoplastic resin composition is injection molded at a molding temperature of 220 to 250°C and a mold temperature of 65°C, and the surface is polished with a polishing grit of 8000 to obtain a 2 mm-thick plate sample, which has a total light transmittance of 89% or more as measured in accordance with JIS K7361. [9] The method according to any one of claims 1 to 4, characterized in that the methacrylic resin (A) and the thermoplastic polyurethane (B) are blended at a temperature in the range of 200 to 260°C. [8] 13. A method for producing the thermoplastic resin composition according to any one of claims 1 to 12.

[10] From [1] [8] A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 5.

[11] From [1] [8] An injection-molded article comprising the thermoplastic resin composition according to any one of claims 1 to 4.

[12] From [1] [8] 2. A method for producing an injection-molded article, comprising molding the thermoplastic composition according to any one of 1 to 11 above at a cylinder temperature of 200 to 260°C. Effect of the Invention

[0009] The thermoplastic resin composition of the present invention exhibits high transmittance and low haze at the same time, and is excellent in transparency, scratch resistance and toughness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Thermoplastic resin composition] The thermoplastic resin composition of the present embodiment contains 50 to 99 mass% of a methacrylic resin (A) and 1 to 50 mass% of a thermoplastic polyurethane (B) relative to 100 mass% of the thermoplastic resin composition. The methacrylic resin (A) is composed of 80.0 to 99.9 mass% of a methacrylic acid ester monomer unit, 0.1 to 20.0 mass% of a vinyl monomer unit composed of a vinyl monomer copolymerizable with a methacrylic acid ester monomer other than maleic acid and maleic anhydride, and 0 to 4.0 mass% of a maleic acid and / or maleic anhydride monomer unit. The thermoplastic polyurethane (B) has a structural unit derived from a polyester polyol and a structural unit derived from an isocyanate having an alicyclic ring. In this specification, the total mass of all components of the thermoplastic resin composition is 100 mass%, unless otherwise specified.

[0011] <Methacrylic resin (A)> The methacrylic resin (A) may contain at least one type of methacrylic resin, and one type of methacrylic resin may be used alone, or two or more types of methacrylic resins may be used in combination. The methacrylic resin (A) must be composed of 80.0 to 99.9 mass% of methacrylic acid ester monomer units, 0.1 to 20.0 mass% of vinyl monomer units consisting of vinyl monomers copolymerizable with methacrylic acid ester monomers excluding maleic acid and maleic anhydride, and 0 to 4.0 mass% of maleic acid and / or maleic anhydride monomer units, relative to 100 mass% of the methacrylic resin. By having the content of methacrylic acid ester monomer units of 99.9% by mass or less, it is possible to prevent the decomposition of the resin during molding, and to effectively prevent the generation of volatile methacrylic acid ester monomers and molding defects called "silver". In addition, by having the content of methacrylic acid ester monomer units of 80.0% by mass or more, it is possible to ensure the heat resistance generally required for molded products. By having sufficient heat resistance, it is possible to ensure rigidity and the strength generally required for molded products.

[0012] Examples of methacrylic acid ester monomers constituting the methacrylic acid ester monomer units contained in the methacrylic resin (A) include, but are not limited to, butyl methacrylate, ethyl methacrylate, methyl methacrylate, propyl methacrylate, isopropyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, 2-ethylhexyl methacrylate, t-butylcyclohexyl methacrylate, benzyl methacrylate, 2,2,2-trifluoroethyl methacrylate, etc. Among these, methyl methacrylate and ethyl methacrylate are preferred from the viewpoints of availability and price. The above methacrylic acid ester monomers may be used alone or in combination of two or more.

[0013] The content of the methacrylic acid ester monomer unit is preferably 85.0 to 99.9 mass%, more preferably 85.0 to 99.8 mass%, even more preferably 85.0 to 99.5 mass%, still more preferably 90.0 to 99.5 mass%, and even more preferably 93.0 to 99.5 mass%, relative to 100 mass% of the methacrylic resin (A). From the viewpoint of obtaining a higher transmittance and at the same time a lower haze, the content is particularly preferably 95.5 to 99.0 mass%.

[0014] The vinyl monomer copolymerizable with the methacrylic acid ester monomer constituting the vinyl monomer unit contained in the methacrylic resin (A) is a vinyl monomer other than maleic acid and maleic anhydride, and examples thereof include, but are not limited to, acrylic acid ester monomers having one acrylate group, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, and 2-ethylhexyl acrylate. Other examples of the acrylic acid ester monomer include those having two or more (meth)acrylate groups, in which both terminal hydroxyl groups of ethylene glycol or its oligomers are esterified with acrylic acid or methacrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; those in which hydroxyl groups of two alcohols, such as neopentyl glycol di(meth)acrylate and di(meth)acrylate, are esterified with acrylic acid or methacrylic acid; and those in which polyhydric alcohol derivatives, such as trimethylolpropane and pentaerythritol, are esterified with acrylic acid or methacrylic acid. In particular, methyl acrylate, ethyl acrylate, and n-butyl acrylate are preferred, and methyl acrylate and ethyl acrylate are more preferred because of their easy availability. The vinyl monomer (preferably, an acrylic ester monomer) copolymerizable with the methacrylic ester monomer may be used alone or in combination of two or more kinds.

[0015] The content of the vinyl monomer unit consisting of the vinyl monomer copolymerizable with the methacrylic acid ester monomer (preferably the content of the acrylic acid ester monomer) is required to be 0.1 to 20.0 mass% relative to 100 mass% of the methacrylic resin (A), preferably 0.1 to 15.0 mass%, more preferably 0.2 to 15.0 mass%, and even more preferably 0.5 to 7.0 mass%, and from the viewpoint of obtaining a higher transmittance and a lower haze at the same time, it is particularly preferable that it is 1.0 to 6.5 mass%. By being 0.1 mass% or more, it is possible to prevent the decomposition of the methacrylic resin during molding, and the degradation due to the decomposition and yellowing of the thermoplastic polyurethane caused by radicals generated by the decomposition of the methacrylic resin, and it is possible to effectively prevent the occurrence of molding defects due to yellowing of the thermoplastic resin composition and the generation of volatile components. In addition, by having the vinyl monomer unit be 20.0 mass% or less, it is possible to ensure the heat resistance generally required for molded products. In addition, the content of the vinyl monomer unit is preferably 0.4% by mass or less, particularly when a monomer having two (meth)acrylate groups is used, 0.25% by mass or less, when a monomer having three (meth)acrylate groups is used, and 0.15% by mass or less, when a monomer having four or more (meth)acrylate groups is used, relative to the methacrylic resin (A) (100% by mass), from the viewpoints of ensuring flowability during injection molding and maintaining transparency.

[0016] Furthermore, examples of vinyl monomers other than acrylic acid ester monomers that are copolymerizable with the above-mentioned methacrylic acid ester monomers other than maleic acid and maleic anhydride include, but are not limited to, α,β-unsaturated acids such as acrylic acid and methacrylic acid; unsaturated group-containing divalent carboxylic acids and alkyl esters thereof such as fumaric acid, itaconic acid, and cinnamic acid; styrene-based monomers such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, and isopropenylbenzene (α-methylstyrene); Examples of the vinyl compounds include aromatic vinyl compounds such as 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, and isopropenyloctylbenzene; vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acid anhydrides such as itaconic anhydride; maleimide, and N-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide; amides such as acrylamide and methacrylamide; and polyfunctional monomers such as divinylbenzene.

[0017] The methacrylic resin (A) may optionally contain maleic acid and / or maleic anhydride monomer units. Maleic acid and maleic anhydride can be copolymerized with methacrylic acid ester monomers. However, from the viewpoints of preventing yellowing when formed into a thermoplastic resin composition with thermoplastic polyurethane, preventing yellowing and silvering during molding and processing, and maintaining good weather resistance, they cannot be used in excess. Therefore, the content of maleic acid monomer units and / or maleic anhydride monomer units is preferably 0 to 4.0 mass%, more preferably 3.0 mass% or less, and even more preferably 2.0 mass% or less, relative to 100 mass% of the methacrylic resin (A), and may not be contained at all.

[0018] In the methacrylic resin (A), a vinyl monomer other than the vinyl monomers exemplified above may be appropriately added and copolymerized for the purpose of improving properties such as heat resistance, moldability, etc. The acrylic ester monomer copolymerizable with the methacrylic ester monomer and the vinyl monomer other than the acrylic ester monomers exemplified above may be used alone or in combination of two or more.

[0019] The total mass ratio of the methacrylic acid ester monomer units and the acrylic acid ester monomer units in 100 mass% of the methacrylic resin (A) is preferably 88 mass% or more, more preferably 94 mass% or more, and even more preferably 100 mass%, from the viewpoint of obtaining a molded product having even more excellent transparency and haze.

[0020] The content of the methacrylic resin (A) in the thermoplastic resin composition of this embodiment may be 50 to 99% by mass relative to 100% by mass of the thermoplastic resin composition. From the viewpoint of obtaining a molded article having excellent transparency and toughness, the content is preferably 50 to 95% by mass, more preferably 55 to 95% by mass, and even more preferably 60 to 90% by mass, and from the viewpoint of obtaining a molded article having excellent transparency, toughness, and scratch resistance, the content is further preferably 66 to 89% by mass, and particularly preferably 71 to 88% by mass.

[0021] (Weight average molecular weight) The weight average molecular weight (Mw) of the methacrylic resin (A) contained in the methacrylic resin composition of this embodiment will be described. The methacrylic resin (A) preferably has a weight average molecular weight (Mw) of 50,000 to 250,000 as measured by GPC (gel permeation chromatography). In order to obtain good mechanical strength and solvent resistance when made into a thermoplastic resin composition, the lower limit of the weight average molecular weight (Mw) of the methacrylic resin (A) is preferably 50,000 or more, more preferably 70,000 or more, and even more preferably 85,000 or more. In order for the methacrylic resin composition to exhibit good fluidity, the upper limit of the weight average molecular weight (Mw) of the methacrylic resin (A) is preferably 250,000 or less, more preferably 230,000 or less, and even more preferably 190,000 or less. By making the weight average molecular weight (Mw) of the methacrylic resin (A) within the range of 50,000 to 250,000, it is possible to achieve a balance between flowability, mechanical strength, and solvent resistance when the resin is made into a thermoplastic resin composition, and good molding processability is maintained.

[0022] (molecular weight distribution) The molecular weight distribution (Mw / Mn) of the methacrylic resin (A) contained in the methacrylic resin composition of this embodiment is preferably 1.0 to 6.0, more preferably 1.0 to 5.5, even more preferably 1.0 to 5.0, and from the viewpoint of further improving moldability, particularly preferably 1.01 to 1.96. When the molecular weight distribution (Mw / Mn) of the methacrylic resin (A) is 1.0 to 6.0, the physical properties exhibited by the methacrylic resin (A) are stable. Here, Mw represents the weight average molecular weight, and Mn represents the number average molecular weight. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin (A) can be measured by GPC, specifically, by the method described in the examples below. Specifically, a calibration curve is created from the elution time and weight average molecular weight using a standard methacrylic resin with a known monodisperse weight average molecular weight and an analytical gel column that elutes high molecular weight components first. Based on the calibration curve, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin (A) to be measured can be calculated, and the molecular weight distribution (Mw / Mn) can be calculated from these. The number average molecular weight (Mn) is simply the average molecular weight per molecule, and is defined as the total weight of the system / the number of molecules in the system. The weight average molecular weight (Mw) is defined as the average molecular weight by weight fraction.

[0023] (Unsaturated double bond terminal amount) The amount of unsaturated double bond terminals in the methacrylic resin (A) is preferably 0.01 mol% or less, more preferably 0.009 mol% or less, and even more preferably 0.008 mol% or less, in order to effectively prevent yellowing of the thermoplastic resin composition caused by radicals generated by decomposition of the methacrylic resin (A) causing decomposition or deterioration of the thermoplastic polyurethane (B) in the thermoplastic resin composition of this embodiment, and molding defects derived from monomers caused by decomposition of the thermoplastic resin composition. The amount of unsaturated double bond terminals can be controlled by controlling the polymerization temperature or using a chain transfer agent. In order to reduce the amount of unsaturated double bond terminals, specifically, when the methacrylic resin (A) is produced by a suspension polymerization method, the polymerization temperature is preferably 80°C or less, more preferably 75°C or less, and even more preferably 70°C or less. The polymerization temperature may be constant, but it is also effective to reduce the amount of unsaturated double bond terminals by setting the polymerization temperature to 70°C or less at the beginning of polymerization. As for the polymerization initiator, it is preferable to produce the methacrylic resin (A) at 0.5% by mass or less, more preferably 0.3% by mass or less, even more preferably 0.25% by mass or less, and particularly preferably 0.23% by mass or less, based on 100% by mass of the methacrylic resin (A). When the solution polymerization method is used, the polymerization temperature is preferably 185°C or less, more preferably 180°C or less, even more preferably 170°C or less, and particularly preferably 160°C or less. The polymerization initiator is preferably prepared at 0.4% by mass or less, more preferably 0.2% by mass or less, further preferably 0.15% by mass or less, particularly preferably 0.1% by mass or less, based on 100% by mass of the methacrylic resin (A). The amount of unsaturated double bond terminals can be measured by the method described in the Examples below.

[0024] (Methacrylic resin (A) production method) The methacrylic resin (A) contained in the methacrylic resin composition of the present embodiment can be produced by, but is not limited to, a solution polymerization method, a bulk polymerization method, a cast polymerization method, or a suspension polymerization method. Bulk polymerization, solution polymerization, and suspension polymerization methods are preferred.

[0025] The polymerization temperature may be appropriately selected as the optimum polymerization temperature depending on the polymerization method, but is preferably 50°C or higher and 185°C or lower, more preferably 50°C or higher and 180°C or lower, and even more preferably 60°C or higher and 170°C or lower. By setting the polymerization temperature at 185°C or lower, the amount of unsaturated double bond terminals can be reduced, and yellowing of the thermoplastic resin composition and molding defects due to deterioration of the thermoplastic polyurethane (B) can be effectively prevented. In addition, by setting the temperature at 50°C or higher, the methacrylic resin can be produced with good productivity.

[0026] A polymerization initiator may be used when producing the methacrylic resin (A). The polymerization initiator is not limited to the following, but in the case of radical polymerization, for example, di-t-butyl peroxide, lauroyl peroxide, stearyl peroxide, benzoyl peroxide, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, dilauroyl peroxide, dicumyl peroxide, t-butyl peroxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethyl peroxide, t-butyl peroxy-2-ethylhexanoate ... Examples of the radical polymerization initiator include organic peroxides such as t-butylcyclohexane and 1,1-bis(t-butylperoxy)cyclohexane, and general azo-based radical polymerization initiators such as azobisisobutyronitrile, azobisisovaleronitrile, 1,1-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis-4-methoxy-2,4-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, and 2,2'-azobis-2-methylbutyronitrile. These initiators may be used alone or in combination of two or more. These radical polymerization initiators may be used in combination with a suitable reducing agent as a redox-based initiator. These radical polymerization initiators and / or redox initiators are generally used in the range of 0 to 1 part by mass per 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin (A), and can be appropriately selected in consideration of the temperature at which the polymerization is carried out and the half-life of the polymerization initiator.

[0027] When bulk polymerization, cast polymerization, or suspension polymerization is selected as the polymerization method for the methacrylic resin (A), it is preferable to carry out the polymerization using a peroxide polymerization initiator from the viewpoint of preventing coloration of the methacrylic resin (A). The peroxide polymerization initiator is not limited to the following, but examples thereof include lauroyl peroxide, decanoyl peroxide, and t-butylperoxy-2-ethylhexanoate, with lauroyl peroxide being more preferred.

[0028] When the methacrylic resin (A) is polymerized by a solution polymerization method at a high temperature of 90°C or higher, it is preferable to use as the polymerization initiator a peroxide, an azobis initiator, or the like, which has a 10-hour half-life temperature of 80°C or higher and is soluble in the organic solvent used. Examples of the peroxide and azobis initiator include, but are not limited to, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, cyclohexane peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 1,1-azobis(1-cyclohexanecarbonitrile), and 2-(carbamoylazo)isobutyronitrile.

[0029] When producing the methacrylic resin (A), the molecular weight of the methacrylic resin (A) may be controlled within a range that does not impair the object of the present invention. Methods for controlling the molecular weight of the methacrylic resin (A) include, but are not limited to, the following, for example, a method for controlling the molecular weight by using chain transfer agents such as alkyl mercaptans, dimethylacetamide, dimethylformamide, and triethylamine, and iniferters such as dithiocarbamates, triphenylmethylazobenzene, and tetraphenylethane derivatives. It is also possible to adjust the molecular weight by adjusting the amount of these additives. As the chain transfer agent, from the viewpoint of handleability and stability, alkyl mercaptans are preferred. Examples of the alkyl mercaptans include, but are not limited to, n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-tetradecyl mercaptan, n-octadecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane tris(thioglycolate), pentaerythritol tetrakis(thioglycolate), and the like. These can be added appropriately depending on the molecular weight of the target methacrylic resin, but are generally used in the range of 0.001 parts by mass to 5 parts by mass per 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin. Other molecular weight control methods include changing the polymerization method, adjusting the amounts of the polymerization initiator, the chain transfer agent, the iniferter, etc., and changing various polymerization conditions such as the polymerization temperature. These molecular weight control methods may be used alone or in combination of two or more.

[0030] <Thermoplastic polyurethane (B)> In this embodiment, the thermoplastic polyurethane (B) is contained in the thermoplastic resin composition. The thermoplastic polyurethane (B) contains a structural unit derived from a polyester polyol and a structural unit derived from an isocyanate having an alicyclic ring, and in order to improve the transparency of the thermoplastic resin composition, the structural unit derived from an isocyanate having one alicyclic ring is preferably 70% by mass or more when the structural units derived from all isocyanates are taken as 100% by mass. When the structural units derived from all isocyanates are taken as 100% by mass, the structural unit derived from an isocyanate having one alicyclic ring is more preferably 75% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 100% by mass. The thermoplastic polyurethane (B) may be at least one type of thermoplastic polyurethane, and one type of thermoplastic polyurethane may be used alone, or two or more types of thermoplastic polyurethane may be used in combination.

[0031] Thermoplastic polyurethanes are usually produced by reacting the following components: (a) isocyanate, (b) a compound reactive with isocyanate, and, optionally, in the presence of at least one (c) catalyst and / or (d) conventional auxiliary and / or additive. The following components: (a) isocyanate and (b) a compound reactive with isocyanate are called structural components. Methods for identifying these structural components include conventionally known methods, such as, but not limited to, the method described in the Journal of the Adhesion Society of Japan, Vol. 40, No. 6 (2004).

[0032] As the (a) isocyanate, from the viewpoint of transparency (high total light transmittance and low haze) and scratch resistance of the thermoplastic resin composition, it is preferable to use an isocyanate having an alicyclic ring in the structure, and it is more preferable to use an isocyanate having an alicyclic ring but no unsaturated carbon bond or aromatic ring. Although not limited to the following, specifically, 4,4-diisocyanatodicyclohexylmethane (H12MDI), 1,3-bisisocyanatomethylcyclohexane (XDI), and isophorone diisocyanate (IPDI) are preferable from the viewpoint of further excellent scratch resistance and transparency, and 1,3-bisisocyanatomethylcyclohexane (XDI) and isophorone diisocyanate (IPDI) are more preferable. The isocyanate may be an isocyanate having 5% by mass or less of a mixture or additive in the isocyanate, as long as it does not impair the effects of the present invention.

[0033] The number of alicyclic rings contained in the (a) isocyanate is preferably 1 to 4, and more preferably 1 in order to improve the heat distortion resistance, the transparency of the thermoplastic resin composition, and the yellowing resistance during thermal processing. In addition, when the (a) isocyanate contains multiple types of isocyanates having alicyclic rings, the number of alicyclic rings may be the number of alicyclic rings of the compound having the largest molar fraction among the compounds contained in the (a) isocyanate.

[0034] (b) As the compound having reactivity with isocyanate, at least one type of polyester polyol can be mentioned. By using the polyester polyol, the transparency of the thermoplastic resin composition becomes good. In the present invention, it is necessary that the structure of the thermoplastic polyurethane (B) contains a structural unit derived from the polyester polyol or a mixture of two or more of them. The polyester polyol includes a polycarbonate diol.

[0035] The mass proportion of the structural units derived from the polyester polyol in 100 mass% of the structural units derived from the polyol contained in the above thermoplastic polyurethane (B) is preferably 80 to 100 mass%, more preferably 90 to 100 mass%, and even more preferably 95 to 100 mass%. The mass proportion of polyether-derived structural units in 100 mass% of polyol-derived structural units contained in the above thermoplastic polyurethane (B) is preferably less than 5 mass%, more preferably less than 2 mass%, even more preferably less than 1 mass%, and it is particularly preferable that none is contained.

[0036] Examples of polyester polyols include polyester polyols produced from an organic dicarboxylic acid having 2 to 12 carbon atoms (preferably an aromatic dicarboxylic acid having 8 to 12 carbon atoms) and a polyhydric alcohol (preferably a diol having 2 to 12 carbon atoms, more preferably a diol having 2 to 6 carbon atoms). The organic dicarboxylic acids include succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, maleic acid, fumaric acid, phthalic acid, isophthalic acid, terephthalic acid, and isomers of naphthalenedicarboxylic acid. The dicarboxylic acids are used alone or in mixtures with other dicarboxylic acids. Instead of free dicarboxylic acids, corresponding dicarboxylic acid derivatives, such as dicarboxylic acid esters of alcohols having 1 to 4 carbon atoms, or dicarboxylic acid anhydrides, can also be used. The polyhydric alcohol is preferably a diol. The diol includes ethanediol, diethylene glycol, 1,2- and 1,3-propanediol, dipropylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, glycerol, and trimethylolpropane, and is preferably ethylene glycol, 1,3-propanediol, methyl-1,3-propanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, or 1,6-hexanediol. The polyhydric alcohol may be a polyester diol produced from a lactone (e.g., ε-caprolactone), or a hydroxycarboxylic acid (e.g., ω-hydroxycarboxylic acid, hydroxybenzoic acid).

[0037] In the production of polyester polyol, the reaction conditions of organic dicarboxylic acid and polyalcohol may be selected in such a way that the polyester polyol produced does not have free acid groups. The actual functionality of the polyester polyol produced is preferably 1.9 to 2.1, more preferably 2.0.

[0038] In the production of polyester polyols, a mixture of an organic dicarboxylic acid and a polyalcohol may be polycondensed in the presence or absence of a catalyst, preferably in the presence of a catalyst, more preferably in the presence of an esterification catalyst. In the production of the polyester polyol, a mixture of an organic dicarboxylic acid and a polyalcohol may be polycondensed under an atmosphere of an inert gas (eg, nitrogen, carbon monoxide, helium, argon, etc.). The temperature during the condensation polymerization of the organic dicarboxylic acid and the polyalcohol is preferably 150 to 250° C., more preferably 180 to 220° C. The condensation polymerization can be carried out under reduced pressure as desired. The condensation polymerization is typically continued until a desired acid number is reached (eg, an acid number of less than 10, preferably an acid number of less than 2). The molar ratio of the organic dicarboxylic acid to the polyalcohol used in the above condensation polymerization is preferably 1:1 to 1.8, and more preferably 1:1.05 to 1.2.

[0039] In particular, it is preferred that the thermoplastic polyurethane (B) contains structural units derived from a polyester polyol produced from ε-caprolactone and / or structural units derived from a condensate of adipic acid or sebacic acid with at least one polyhydric alcohol selected from the group consisting of ethylene glycol, 1,3-propanediol, methyl-1,3-propanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, and 1,6-hexanediol.

[0040] The number average molecular weight Mn of the polyester polyol used is preferably 500 to 4,000, more preferably 650 to 3,500, and further preferably 800 to 3,000. The number average molecular weight Mn can be measured by a GPC method.

[0041] (b) As a compound having reactivity with isocyanate, in addition to polyester polyol, polyhydric alcohol can be mentioned. Among polyhydric alcohols, at least one polyhydric alcohol selected from the group consisting of ethylene-1,2-diol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanediol, 1,4-dimethanolcyclohexane, and neopentyl glycol is preferred. Polyhydric alcohols selected from the group consisting of ethylene-1,2-diol, 1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol are more preferred. The polyhydric alcohol functions as a chain extender.

[0042] In the thermoplastic resin composition of the present embodiment, it is preferable that the thermoplastic polyurethane (B) contains a structural unit derived from at least one polyhydric alcohol selected from the group consisting of ethylene-1,2-diol, 1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol as a polyol.

[0043] The (c) catalyst is preferably a (c) catalyst that accelerates the reaction between (a) the NCO group of the isocyanate and (b) the hydroxy group of the compound reactive to the isocyanate. The (c) catalyst includes tertiary amines, and is preferably triethylamine, dimethylcyclohexylamine, N-methylmorpholine, N,N'-dimethylpiperazine, 2-(dimethylaminoethoxy)ethanol or diazabicyclo[2.2.2]octane. The (c) catalyst is preferably an organometallic compound (e.g., titanate ester, iron compound (preferably iron(III) acetylacetonate), tin compound (preferably tin diacetate, tin dioctoate, tin dilaurate) or dialkyltin salt of aliphatic carboxylic acid (preferably dibutyltin diacetate, dibutyltin dilaurate), bismuth salt in which bismuth is preferably present in the oxidation state of 2 or 3, particularly 3).

[0044] The catalyst (c) is preferably a salt of a carboxylic acid. The carboxylic acid is preferably a carboxylic acid having 6 to 14 hydrocarbons, particularly preferably 8 to 12 hydrocarbons. The salt of a carboxylic acid is preferably a bismuth salt, and examples of suitable bismuth salts are bismuth (III) neodecanoate, bismuth 2-ethylhexanoate, and bismuth octanoate.

[0045] As the (c) catalyst used in the production of the thermoplastic polyurethane (B), a tin catalyst, particularly tin dioctoate, is preferably used, and the mass ratio is preferably 0.0001 to 0.1 parts by mass relative to 100 parts by mass of the (b) compound having reactivity with isocyanate. When a tertiary amine is used as the (c) catalyst, from the viewpoint of preventing the tertiary amine from being incorporated into the structural skeleton of the thermoplastic polyurethane (B) and yellowing during molding of the thermoplastic resin composition, the tertiary amine content in 100% by mass of the thermoplastic resin composition of this embodiment is preferably 0.9% by mass or less, more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0% by mass. In addition, from the viewpoint of preventing yellowing during molding, the content of the tertiary amine contained in 100% by mass of the thermoplastic polyurethane (B) is preferably 0.9% by mass or less, more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0% by mass.

[0046] In producing the thermoplastic polyurethane (B), the ratio of the structural components (a) and (b) is preferably such that the equivalent ratio of the NCO groups of the isocyanate (a) to the total hydroxyl groups of the structural component (b) is 0.9 to 1.1: 1, more preferably 0.95 to 1.05: 1, and even more preferably 0.96 to 1.0: 1. The thermoplastic polyurethane (B) is preferably produced by reacting in the presence of a catalyst (c) and, optionally, an auxiliary and / or additive (d).

[0047] The content of the thermoplastic polyurethane (B) in the thermoplastic resin composition of this embodiment is 1 to 50 mass%, relative to 100 mass% of the thermoplastic resin composition. From the viewpoint of obtaining a molded article having good toughness and transparency, the content is preferably 5 to 50 mass%, more preferably 5 to 45 mass%, and even more preferably 10 to 40 mass%. From the viewpoint of obtaining a molded article having good toughness, transparency and scratch resistance, the content is further preferably 11 to 34 mass%, and particularly preferably 12 to 29 mass%.

[0048] The total content of the methacrylic resin (A) and the thermoplastic polyurethane (B) in the thermoplastic resin composition of this embodiment is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 100 mass%, relative to 100 mass% of the thermoplastic resin composition.

[0049] <Other ingredients> The thermoplastic resin composition of the present embodiment may contain other components in addition to the methacrylic resin (A) and the thermoplastic polyurethane (B) as long as the effects of the present invention are not impaired. As the other components, other conventionally known resins can be mixed. The other resin is not particularly limited, and known curable resins and thermoplastic resins are suitably used. Examples of thermoplastic resins include, but are not limited to, polypropylene-based resins, polyethylene-based resins, polystyrene-based resins, syndiotactic polystyrene-based resins, ABS-based resins, methacrylic-based resins, AS-based resins, BAAS-based resins, MBS resins, AAS resins, biodegradable resins, polycarbonate-ABS resin alloys, polyalkylene arylate-based resins such as polybutylene terephthalate, polyethylene terephthalate, polypropylene terephthalate, polytrimethylene terephthalate, and polyethylene naphthalate, polyamide-based resins, polyphenylene ether-based resins, polyphenylene sulfide-based resins, and phenol-based resins. In particular, AS resin and BAAS resin are preferred for improving flowability, ABS resin and MBS resin are preferred for improving impact resistance, and polyester resin is preferred for improving chemical resistance. Furthermore, polyphenylene ether resins, polyphenylene sulfide resins, phenol resins, and the like have the effect of improving flame retardancy. Furthermore, examples of the curable resin include, but are not limited to, unsaturated polyester resin, vinyl ester resin, diallyl phthalate resin, epoxy resin, cyanate resin, xylene resin, triazine resin, urea resin, melamine resin, benzoguanamine resin, urethane resin, oxetane resin, ketone resin, alkyd resin, furan resin, styrylpyridine resin, silicone resin, synthetic rubber, and the like. These resins may be used alone or in combination of two or more kinds.

[0050] In order to impart various predetermined properties such as rigidity and dimensional stability to the thermoplastic resin composition of the present embodiment, various additives other than the methacrylic resin (A) and the thermoplastic polyurethane (B) may be mixed within a range that does not impair the effects of the present invention. Examples of additives include, but are not limited to, plasticizers such as phthalate esters, fatty acid esters, trimellitate esters, phosphate esters, and polyesters; release agents such as higher fatty acids, higher fatty acid esters, and higher fatty acid mono-, di-, or triglycerides; antistatic agents such as polyethers, polyether esters, polyether ester amides, alkyl sulfonates, and alkylbenzene sulfonates; stabilizers such as phosphine stabilizers and light stabilizers; flame retardants; flame retardant assistants; curing agents; curing accelerators; conductivity imparting agents; stress relaxation agents; crystallization accelerators; dyes; hydrolysis inhibitors; lubricants; ultraviolet absorbers; antioxidants; impact resistance imparting agents; sliding improvers; compatibilizers; nucleating agents; reinforcing agents; reinforcing agents; flow adjusters; sensitizers; coloring pigments; rubber polymers; thickeners; anti-settling agents; anti-sagging agents; fillers; defoamers; coupling agents; rust inhibitors; antibacterial and anti-fungal agents; antifouling agents; conductive polymers; and carbon black. In particular, an impact resistance imparting agent such as an acrylic rubber multilayer polymer is preferred.

[0051] The content of the above-mentioned other components in the thermoplastic resin composition for obtaining the molded article made of the thermoplastic resin composition of the present embodiment is preferably 0 to 40 mass%, more preferably 0.01 to 30 mass%, and even more preferably 0.02 to 25 mass%, relative to 100 mass% of the thermoplastic resin composition, in order to maintain the transparency of the thermoplastic resin composition and prevent molding defects such as bleed-out. By containing them in the above ranges, the functions of each material can be exhibited. In order to effectively impart impact resistance while ensuring transparency, the impact resistance imparting agent is preferably used in an amount of 3 to 50 mass%, more preferably 5 to 20 mass%, and even more preferably 5 to 9 mass%, relative to 100 mass% of the thermoplastic resin composition.

[0052] The thermoplastic resin composition of the present embodiment, when formed into a flat plate sample, preferably has a total light transmittance of 89% or more, more preferably 90% or more, and even more preferably 91% or more. The total light transmittance can be adjusted, for example, by setting the mass ratio of the methacrylic resin (A) and the thermoplastic polyurethane (B) in the preferred range described above, using the preferred example of the methacrylic resin (A) described above, or the like. The total light transmittance can be measured by the method described in the Examples section below.

[0053] The thermoplastic resin composition of the present embodiment, when formed into a flat plate sample, preferably has a haze of 10% or less, more preferably 9% or less, further preferably 8% or less, and particularly preferably 3.5% or less. The haze can be adjusted, for example, by setting the mass ratio of the methacrylic resin (A) and the thermoplastic polyurethane (B) in the preferred range described above, by using the preferred example of the methacrylic resin (A) described above, or the like. The haze can be measured by the method described in the Examples below.

[0054] <Method of producing thermoplastic resin composition> The thermoplastic resin composition can be obtained by mixing and kneading the methacrylic resin (A) and the thermoplastic polyurethane (B), and, if necessary, the various additives described above and other resins. For example, the composition can be produced by kneading using a kneading machine such as an extruder, a heating roll, a kneader, a roller mixer, or a Banbury mixer. In particular, kneading with an extruder is preferred from the viewpoint of productivity. The kneading temperature (i.e., the temperature when the methacrylic resin (A) and the thermoplastic polyurethane (B) are mixed) is preferably 170°C or higher, more preferably 180°C or higher, and even more preferably 200°C or higher, from the viewpoint of productivity. Moreover, from the viewpoint of preventing deterioration of the methacrylic resin (A) and the thermoplastic polyurethane (B) and volatilization of various additives, it is preferably 290°C or lower, more preferably 280°C or lower, and even more preferably 260°C or lower. In the present embodiment, the kneading temperature refers to the set temperature at the center of the cylinder when an extruder is used.

[0055] <Molded body> The molded article of the present embodiment is characterized by containing the thermoplastic resin composition of the present embodiment. The molded article may be an injection molded article.

[0056] <Method of manufacturing molded body> The molded article of the present embodiment can be produced by a known molding method. Known molding methods include, but are not limited to, injection molding, extrusion molding, blow (hollow) molding, vacuum molding, compression molding, calendar molding, inflation molding, etc. In particular, molding by injection molding is preferred from the viewpoint of productivity. From the viewpoint of productivity, the molding temperature is preferably 170° C. or higher, more preferably 190° C. or higher, and even more preferably 200° C. or higher. From the viewpoint of preventing deterioration of the methacrylic resin (A) and the thermoplastic polyurethane (B) and volatilization of various additives, the molding temperature is preferably 290° C. or lower, more preferably 280° C. or lower, and even more preferably 260° C. or lower. From the viewpoint of productivity, the cylinder temperature during molding is preferably 170° C. or higher, more preferably 190° C. or higher, and even more preferably 200° C. or higher. From the viewpoint of preventing deterioration of the methacrylic resin (A) and the thermoplastic polyurethane (B) and volatilization of various additives, the cylinder temperature is preferably 290° C. or lower, more preferably 280° C. or lower, and even more preferably 260° C. or lower.

[0057] <Applications of molded products> The molded article containing the thermoplastic resin composition of the present embodiment has good weather resistance, scratch resistance, and transparency, and can have excellent long-term stability against an outdoor environment exposed to ultraviolet rays. Therefore, the molded article can be suitably used for vinyl house films, liquid crystal protective films, building materials, vehicle materials, electrical and electronic materials, lighting materials, etc. Specific applications of the molded article of the present embodiment include, for example, roofing materials used in buildings, automobiles, trains, or buses, protective materials used in lighting, signs, and meters, vehicle lighting materials, ship lighting materials, battery protective covers, etc. It is particularly preferable to use the molded article as a vehicle material or a vehicle lighting material.

[0058] Further embodiments of the invention can be found in the claims and examples. The above-mentioned features of the articles, methods and methods of use according to the invention and the features described below can of course be used not only in the respective combinations described, but also in other combinations without going beyond the scope of the invention. Thus, for example, the invention also implicitly includes combinations of preferred features with particularly preferred features, or combinations of features not specifically characterized with particularly preferred features, etc., even if the combinations are not explicitly described. EXAMPLES

[0059] Examples of the invention are given below which are not limiting, and in particular the invention also includes embodiments resulting from combinations thereof.

[0060] [Raw materials used in the examples and comparative examples] <Raw material for methacrylic resin (A)> The raw materials for the methacrylic resin (A) used in the production of the thermoplastic resin composition are as follows. Methyl methacrylate (MMA): Asahi Kasei (containing 2.5 ppm by mass of 2,4-dimethyl-6-t-butylphenol manufactured by Chugai Boeki as a polymerization inhibitor) Methyl acrylate (MA): manufactured by Mitsubishi Chemical (containing 14 ppm by mass of 4-methoxyphenol manufactured by Kawaguchi Chemical Industry Co., Ltd. as a polymerization inhibitor) Ethyl acrylate (EA): manufactured by Mitsubishi Chemical Maleic anhydride (MAH): Nippon Shokubai n-Octyl mercaptan: Arkema Lauroyl peroxide: NOF Corporation Perhexa 22: NOF Corp. Metaxylene: Tokyo Chemical Industry Co., Ltd. - Tribasic calcium phosphate: Manufactured by Nippon Chemical Industry Co., Ltd., used as a suspending agent Calcium carbonate: Shiraishi Kogyo Co., Ltd., used as a suspending agent Sodium lauryl sulfate: Manufactured by Wako Pure Chemical Industries, used as a suspension aid

[0061] <Thermoplastic polyurethane (B)> Elastollan NY5685N00A: Polyurethane 1 made by F.C.I. Elastollan XCT-A1095: Polyurethane 2 made by F.C.I. Elastollan NY1385V3-10HB: Polyurethane 3 made by F.C.I. Elastollan HD595A10: Polyurethane 4 made by F.C.I.

[0062] [Table 1]

[0063] <Additives> Kane Ace M-210: Kaneka acrylic rubber impact modifier · Tinuvin P: Manufactured by BASF, melting point 128 °C · Stearyl alcohol: Manufactured by Kao Corporation, Calcohol 8098

[0064] [Measurement and evaluation methods] [I. Measurement of the molecular weight of methacrylic resin (A)] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) (Mn is the number average molecular weight) of the methacrylic resin (A) were measured using the following apparatus and conditions. · Measuring apparatus: Gel permeation chromatography (HLC-8320GPC) manufactured by Tosoh Corporation · Measurement conditions: Column: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were connected in series in this order and used. In this column, high molecular weight components elute quickly, and low molecular weight components elute slowly. Detector: RI (differential refractive index) detector Detection sensitivity: 3.0 mV / min Column temperature: 40 °C Sample: A 20 mL solution of 0.02 g of methacrylic resin in tetrahydrofuran Injection volume: 10 μL Developing solvent: Tetrahydrofuran, flow rate; 0.6 mL / min. As an internal standard, 2,6-di-t-butyl-4-methylphenol (BHT) was added at 0.1 g / L. As calibration curve standard samples, the following 10 types of polymethyl methacrylate with known monodisperse peak molecular weights and different molecular weights (manufactured by Polymer Laboratories; PMMA Calibration Kit M-M-10) were used. Note that the polymethyl methacrylate of the standard sample used for the calibration curve is a single peak for each, so the peak corresponding to each was denoted as the weight peak molecular weight Mp. This was distinguished from the peak top molecular weight calculated when there are multiple peaks for one sample. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard data 10 850 Under the above conditions, the RI detection intensity with respect to the elution time of the methacrylic resin (A) was measured. Based on the area of the GPC elution curve and the calibration curve of the third-order approximation formula, the weight-average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the methacrylic resin (A) were determined.

[0065] <II. Analysis of the structural unit of methacrylic resin (A)> 1 The structural unit was identified by 1H-NMR measurement, and its abundance (mass%) was calculated. 1 The measurement conditions for 1H-NMR measurement are as follows. Apparatus: JEOL-ECA500 Solvent: CDCl3-d1 (deuterated chloroform) Sample: 1 g of methacrylic resin (A) was dissolved in 10 ml of acetone, 20 ml of methanol was added dropwise and filtered. 15 mg of the insoluble matter dried under vacuum at 40 °C for 15 hours was dissolved in 0.75 mL of CDCl3-d1 to obtain a measurement sample.

[0066] <III. Amount of unsaturated double bond ends of methacrylic resin (A)> 1 The structural unit was identified by 1H-NMR measurement, and its abundance (mol%) in the methacrylic resin (A) was calculated. The amount of unsaturated double bond ends was calculated from the integral value of the unsaturated double bond end peak (5.4 to 5.6 ppm) and the integral value of the peak of the methyl group bonded to the oxygen atom of the ester group of the methacrylic resin (A) (3.6 ppm). 1 The measurement conditions for 1H-NMR measurement are as follows. Equipment: JEOL-ECA500 Number of scans: 5000 Measurement temperature: room temperature Observed nucleus: 1H (500MHz) Solvent: CDCl3-d1 (deuterated chloroform) Sample: 1 g of methacrylic resin (A) was dissolved in 10 ml of chloroform, 20 ml of methanol was added dropwise, and the solution was filtered. The insoluble matter after filtration was dissolved again in 10 ml of chloroform, 20 ml of methanol was added dropwise, and the filtration was repeated twice. The remaining insoluble matter was vacuum dried at 40°C for 15 hours, and 75 mg of the solution was dissolved in 10.75 mL of CDCl3-d to prepare the measurement sample. If the insoluble matter after the final filtration did not reach 75 mg, the above procedure was repeated until it reached 75 mg.

[0067] <Measurement of total light transmittance> The total light transmittance of a 2 mm thick flat plate sample obtained by the method described below was measured in accordance with JIS K7361 using a Nippon Denshoku NDH7000. Total light transmittance of 91% or more was rated as "◎" (exceptionally excellent), 90% or more was rated as "◯" (good), 89% or more was rated as "△" (level that is acceptable for practical use), and less than 89% was rated as "×" (poor).

[0068] <Haze measurement, scratch resistance measurement> A 2 mm-thick plate sample obtained by the method described below and a reference white slide glass No. 001 manufactured by Matsunami Glass Co., Ltd. were placed so as not to move vertically from the ground, and 22 g of Quarzsand F36 manufactured by Quarzwerke GmbH, 512 g of water, and a stirrer were placed in a spray gun with a nozzle diameter of 1.3 mm, and the plate sample and reference glass were placed so that the Quarzsand F36 hit both the reference glass and the plate sample in the same way, while stirring at a speed of 1000 rpm with a magnetic stirrer, under conditions of an injection pressure of 0.3 MPa, a flow rate of 0.24 L / min, and a distance of 19 cm between the nozzle opening and the sample. The haze before and after the test was measured in accordance with JIS K7136 using Nippon Denshoku's NDH7000, and the change was determined to evaluate the scratch resistance. The haze was measured at the center of the test area where the Quarzsand F36 hit. The test was completed when the haze of the reference glass reached 3. If the haze of the reference glass did not reach 3 in one test, the test was repeated under the same conditions. The scratch resistance was judged as "○" (good) when the change in haze was 7% or less, and "×" (bad) when it exceeded 7%. The change in haze was calculated according to the following formula. (Change in haze (%)) = (Haze after test (%)) - (Haze before test (%)) In addition, the haze was judged by the haze of the thermoplastic resin composition before testing, measured using a 2 mm thick flat plate sample obtained by the method described below. If the haze value was 3% or less, it was judged as "◎" (particularly excellent), if it was more than 3% and less than 8%, it was judged as "〇" (excellent), if it was more than 8% and less than 10%, it was judged as "△" (a level that is acceptable for practical use), and if it was more than 10%, it was judged as "×" (poor).

[0069] <Evaluation of injection moldability> A 2 mm thick plate sample was prepared by the method described below, and when visually inspected, if there was any defect in the appearance of the plate sample or significant yellowing of the pellets was observed, it was rated as "△" (problems with injection moldability), and if there was no defect in appearance, it was rated as "◯" (good). This evaluation makes it possible to evaluate whether the thermoplastic resin composition of this embodiment is suitable for injection molding when it is to be thermally processed.

[0070] <Evaluation of toughness> The ISO dumbbell test piece obtained in the "ISO dumbbell test piece" described later was subjected to a tensile test in accordance with ISO527-1. A Shimadzu Autograph AGS-5kNX was used for the test. The tensile fracture strain or nominal tensile fracture strain was measured five times with a gauge length of 50 mm, and the average value was used as an index of toughness. If the tensile fracture strain or nominal tensile fracture strain was 9% or more, it was rated as "good" (excellent), and if it was less than 9%, it was rated as "poor".

[0071] <Evaluation of yellowing resistance> The pellets of the thermoplastic resin composition were put into an injection molding machine (Toshiba Machine EC-100SX) with the temperature of the center of the cylinder set to 220°C and the mold temperature set to 50°C, and six 100 mm square flat plates with a thickness of 2 mm were molded and discarded. The yellowness of each of the seventh to eleventh plates was measured and the average value YI1 was obtained. The molding cycle was set to 65 seconds. Next, the pellets were put into an injection molding machine (Toshiba Machine EC-100SX) with the temperature of the center of the cylinder set to 250°C and the mold temperature set to 50°C, and six 100 mm square flat plates with a thickness of 2 mm were molded and discarded. The yellowness of each of the seventh to eleventh plates was measured and the average value YI2 was obtained. The molding cycle was set to 65 seconds. ΔYI was calculated from YI2-YI1 and used as an index of thermal stability, and yellowing resistance was evaluated according to the following criteria: ΔYI≦0.5: ◎ (excellent), 0.5<ΔYI<1.5: ◯ (good), 1.5≦ΔYI≦2.0: △ (sufficient thermal stability for practical use), ΔYI<2.0: × (poor). This evaluation allows the difference in yellowness depending on the molding temperature conditions to be understood, and allows the degree of freedom in setting molding conditions to be evaluated when attempting to thermally process the thermoplastic resin composition of this embodiment. The yellowness was measured using a Tokyo Denshoku color difference meter TC-8600A in a C light source 10° visual field transmission mode.

[0072] <Evaluation of processing stability> Pellets of the thermoplastic resin composition were placed in an injection molding machine (Toshiba Machine EC-100SX) with the cylinder center temperature set at 260°C, mold temperature set at 50°C, injection speed set at 30mm / sec, and molding cycle set at 65 sec, and 50 100mm square flat plates with a thickness of 2mm were molded. The number of plates with silver defects was counted and used as an index of thermal processing stability. The processing stability during heat processing was evaluated based on the following criteria: ○ (good) when the number of silver spots was 3 or less, △ (sufficient for practical use) when the number of silver spots was 7 or less, and × (bad) when the number of silver spots was 8 or more. This evaluation allows the evaluation of continuous moldability (productivity) under relatively high molding temperature conditions when attempting to heat process the thermoplastic resin composition of this embodiment.

[0073] The thermoplastic resin composition of the present embodiment can be analyzed for the mass ratio of the methacrylic resin (A) and the thermoplastic polyurethane (B) in the thermoplastic resin composition by the following method. 400 mg of the thermoplastic resin composition is dissolved in 40 mL of tetrahydrofuran. The solution phase contains the methacrylic resin (A), and the swelling layer contains the thermoplastic polyurethane (B). The solution phase is separated by filtration, and the reprecipitated with 350 mL of methanol is dissolved again in 40 mL of tetrahydrofuran and reprecipitated with 350 mL of methanol. This is dried at 60°C under nitrogen blowing to obtain sample A, and its mass is measured. 2 mg of dimethyl sulfone standard substance is added to 10 mg of sample A as a standard substance, and the mixture is dissolved in 1 mL of CDCl3-d1 to obtain measurement sample 1. 1 The mass of the methacrylic resin (A) in 10 mg of sample A is quantified by H-NMR measurement (ECA-500 manufactured by JEOL Ltd.). The mass ratio of the methacrylic resin in 10 mg of sample A is applied to sample A to obtain the mass ratio of the methacrylic resin in the thermoplastic resin composition. At this time, the structure of the methacrylic resin (A) can also be identified. In addition, the mass of the swollen layer was measured for sample B, which was dried at 60°C under nitrogen blowing. 2 mg of bistrimethylsilylbenzene-d4 standard substance was added to 10 mg of sample B, and the mixture was dissolved in 1 mL of deuterated dimethylformamide to obtain measurement sample 2. 1 The mass of thermoplastic polyurethane (B) in 10 mg of sample B is quantified by H-NMR measurement (ECA-500 manufactured by JEOL Ltd.). The mass ratio of the thermoplastic polyurethane in 10 mg of sample B is applied to sample B to determine the mass ratio of the thermoplastic polyurethane (B) in the thermoplastic resin composition. At this time, the structure of the thermoplastic polyurethane (B) can also be identified. If the detailed composition of thermoplastic polyurethane (B) is unclear, the composition can be identified by using IR measurement and pyrolysis GC / MS measurement in combination. In IR measurement, the frozen and crushed sample B is mixed with KBr and made into a tablet, and the IR measurement is performed to identify the composition of thermoplastic polyurethane (B). In pyrolysis GC / MS measurement, 25.0 mg of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is collected in a 100 mL volumetric flask. Dimethylformamide is added to the measuring flask up to the mark line to prepare a 0.025 mass% octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate standard solution. 1 mL of the standard solution is added to sample B and dissolved to prepare the solution for pyrolysis GC / MS measurement. The pyrolysis GC / MS measurement is performed using a double-shot pyrolyzer, with the first step being thermal extraction at 300°C, and the second step being pyrolysis at 500°C, followed by pyrolysis GC / MS measurement to identify the composition of thermoplastic polyurethane (B).

[0074] The mass proportion of the tertiary amine contained in the thermoplastic resin composition of the present embodiment can be measured by the following method. 200 mg of the thermoplastic resin composition was freeze-pulverized and immersed in 10 mL of 0.01 mol% aqueous hydrochloric acid for 3 hours. 0.05 mL of phenolphthalein solution was added thereto, and neutralization titration was performed with 0.01 mol% aqueous sodium hydroxide solution. The amount of hydrochloric acid consumed was calculated from the titration amount, and this was taken as the content of the tertiary amine in the thermoplastic resin composition, and converted into the mass ratio of the tertiary amine in the thermoplastic resin composition. In addition, the mass proportion of the tertiary amine contained in the thermoplastic polyurethane (B) can also be measured. The above sample B is freeze-pulverized and immersed in 10 mL of 0.01 mol% hydrochloric acid aqueous solution for 3 hours. 0.05 mL of phenolphthalein solution is added thereto, and neutralization titration is performed with 0.01 mol% sodium hydroxide aqueous solution. The amount of hydrochloric acid consumed is calculated from the titration amount and regarded as the content of tertiary amine in sample B. The ratio of the content of tertiary amine in sample B to the content of thermoplastic polyurethane (B) is regarded as the mass ratio of tertiary amine in thermoplastic polyurethane (B).

[0075] [Thermoplastic resin composition] The methacrylic resin (A) used as a constituent component of the thermoplastic resin composition in the examples and comparative examples described later will be described below.

[0076] <Methacrylic resin (A)> As the methacrylic resin (A), methacrylic resins (A-1) to (A-6) produced in the following Production Examples A1 to A6 were used.

[0077] (Production Example A1 (Production of Methacrylic Resin (A-1))) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of ion-exchanged water was added to a 60 L reactor, and the temperature was raised to 80° C., and then mixed liquid (a), 21.2 kg of methyl methacrylate, 0.43 kg of methyl acrylate, 27 g of lauroyl peroxide, and 62 g of n-octyl mercaptan were added. Thereafter, polymerization was carried out for 1 hour at an initial polymerization temperature of about 60°C, then the temperature was raised to about 80°C, and suspension polymerization was carried out while maintaining the temperature at about 80°C. After an exothermic peak was observed, the temperature was raised to 92°C at a rate of 1°C / min, and the mixture was aged for 60 minutes, at which point the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C, and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove aggregates, and the resulting bead-like polymer was washed, dehydrated, and dried to obtain polymer microparticles 1. The polymer microparticles 1 were pelletized using a φ26 mm twin-screw extruder set at 240°C to obtain "methacrylic resin (A-1)". The weight-average molecular weight of the resulting resin was 102,000, the molecular weight distribution (Mw / Mn) was 1.85, the structural unit was MMA / MA=98 / 2 by mass%, and the amount of unsaturated double bond terminals was 0.003 mol%.

[0078] (Production Example A2 (Production of Methacrylic Resin (A-2))) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (b). Next, 26 kg of ion-exchanged water was added to a 60 L reactor and the temperature was raised to 80° C., and mixed liquid (b), 20.5 kg of methyl methacrylate, 1.32 kg of ethyl acrylate, 33 g of lauroyl peroxide, and 22.4 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80°C, and after observing an exothermic peak, the temperature was increased to 92°C at a rate of 1°C / min. Thereafter, the mixture was aged for 60 minutes to essentially complete the polymerization reaction. Next, the mixture was cooled to 50°C, and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove aggregates, and the resulting bead-like polymer was washed, dehydrated, and dried to obtain polymer microparticles 2. The polymer microparticles 2 were pelletized using a φ26 mm twin-screw extruder set at 270°C to obtain "methacrylic resin (A-2)". The weight-average molecular weight of the resulting resin was 218,000, the molecular weight distribution (Mw / Mn) was 1.95, the structural unit was MMA / EA=94 / 6% by mass, and the amount of unsaturated double bond terminals was 0.01 mol%.

[0079] (Production Example A3 (Production of Methacrylic Resin (A-3)) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate, to obtain a mixed liquid (c). Next, 26 kg of ion-exchanged water was added to a 60 L reactor, and the temperature was raised to 80° C., and then mixed liquid (c), 21.2 kg of methyl methacrylate, 0.43 kg of methyl acrylate, 27 g of lauroyl peroxide, and 88 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 75° C., and after observing an exothermic peak, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C, and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh to remove aggregates, and the resulting bead-like polymer was washed, dehydrated, and dried to obtain polymer microparticles 3. The polymer microparticles 3 were pelletized using a φ26 mm twin-screw extruder set at 230°C to obtain "methacrylic resin (A-3)". The weight-average molecular weight of the resulting resin was 72,000, the molecular weight distribution (Mw / Mn) was 1.83, the structural unit was MMA / MA=98 / 2 by mass%, and the amount of unsaturated double bond terminals was 0.007 mol%.

[0080] (Production Example A4 (Production of Methacrylic Resin (A-4)) In a pressure-resistant polymerization reactor equipped with an agitator, 950g of methyl methacrylate, 9.6g of methyl acrylate, 0.2g of Perhexa 22 as a polymerization initiator, 2.8g of n-octyl mercaptan, and 240g of metaxylene were charged. The atmosphere in the reaction vessel was replaced with nitrogen, the temperature was raised to 185°C, and the polymerization reaction was carried out for 90 minutes. After removing the contents and cleaning the reactor, the above reaction was repeated five times. The removed contents were subjected to freeze-pulverization, and then pelletized using a φ42mm degassing extruder set at 230°C to obtain "methacrylic resin (A-4)". The weight-average molecular weight of the obtained resin was 76,000, the molecular weight distribution (Mw / Mn) was 1.97, the structural unit was MMA / MA=99 / 1 mass%, and the amount of unsaturated double bond terminals was 0.014 mol%.

[0081] (Production Example A5 (Production of Methacrylic Resin (A-5))) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate, to obtain a mixed liquid (c). Next, 26 kg of ion-exchanged water was put into a 60 L reactor, and the temperature was raised to 80° C., and then the mixed liquid (c), 21.6 kg of methyl methacrylate, 27 g of lauroyl peroxide, and 62 g of n-octyl mercaptan were put into the reactor. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 75° C., and after observing an exothermic peak, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C, and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh to remove aggregates, and the resulting bead-like polymer was washed, dehydrated, and dried to obtain polymer microparticles 4. The polymer microparticles 4 were pelletized using a φ26 mm twin-screw extruder set at 240°C to obtain "methacrylic resin (A-5)". The weight-average molecular weight of the resulting resin was 103,000, the molecular weight distribution (Mw / Mn) was 1.83, the structural unit was MMA = 100% by mass, and the amount of unsaturated double bond terminals was 0.007 mol%.

[0082] (Production Example A6 (Production of Methacrylic Resin (A-6)) Using a vessel equipped with a stirrer, 95 parts by mass of methyl methacrylate, 5 parts by mass of maleic anhydride, 0.05 parts by mass of lauroyl peroxide, and 0.25 parts by mass of n-octyl mercaptan were added and dissolved to prepare a monomer mixture liquid. Meanwhile, a cell was prepared by assembling two glass plates measuring 250 × 300 mm and 6 mm thick, with a flexible polyvinyl chloride gasket attached around their outer periphery so that the distance between the two glass plates was 3.5 mm. The above-mentioned monomer mixture liquid was subjected to a volatilization operation for 2 minutes under a reduced pressure of 50 torr while being stirred. Thereafter, the reduced pressure was released, the pressure was returned to normal, and the mixture was immediately poured into the glass cell to fill it. Next, the resin was kept in a hot water bath adjusted to 60-65°C for 22 hours, and then in a hot air circulating oven adjusted to 110°C for 3 hours. The resin was then left to cool indoors, and the glass plate was removed to obtain a sheet-like resin. The sheet-like resin obtained as described above was pulverized with a coarse pulverizer, Orient Mill VM-42D, manufactured by Seishin Enterprise Co., Ltd., equipped with a 10 mm mesh screen, and then the pulverized material was sieved through a 500 μm sieve to remove fine powder and obtain a pulverized composition. This pulverized composition was pelletized with a φ26 mm twin-screw extruder set at 240 ° C to obtain "methacrylic resin (A-6)". The weight-average molecular weight of the obtained resin was 108,000, the molecular weight distribution (Mw / Mn) was 1.92, the structural unit was MMA / MAH = 95.2 / 4.8 mass%, and the amount of unsaturated double bond terminals was 0.004 mol%.

[0083] [Examples 1-4, 6-12] [Comparative Examples 1-5] The methacrylic resin (A), thermoplastic polyurethane (B), and other additives were weighed out so as to obtain the blending ratios shown in Table 2, and then put into a tumbler and mixed. After thorough mixing, the mixed raw materials were put into a twin-screw extruder of φ26 mm, melt-kneaded (compounded) to generate strands, cooled in a water bath, and cut with a pelletizer to obtain pellets. During compounding, a vacuum line was connected to the vent of the extruder, and volatile components such as moisture and monomer components were removed under conditions of -0.06 MPa. Thus, a thermoplastic resin composition was obtained. The kneading temperature of the thermoplastic resin composition was 230 to 260 ° C. The numerical values ​​in Table 2 represent the blending parts (parts by mass) when the total mass of the methacrylic resin (A) and the thermoplastic polyurethane (B) is 100 parts by mass. The mass proportions of the methacrylic resin (A) and the thermoplastic polyurethane (B) in the thermoplastic resin compositions obtained in Examples 1 to 4, 6 to 9, 11, and 12 and Comparative Examples 1 to 5 were analyzed, and were found to be the same as those shown in Table 2. The mass proportions of the methacrylic resin (A) and the thermoplastic polyurethane (B) in the thermoplastic resin composition obtained in Example 10 were 88% by mass and 12% by mass, respectively. The mass proportions of the tertiary amine in the thermoplastic resin compositions obtained in Examples 1 to 4, 6 to 12, and Comparative Examples 1 to 5 were 0% by mass, and the mass proportions of the tertiary amine in the thermoplastic polyurethane (B) were 0% by mass.

[0084] [Examples 5 and 13] Thermoplastic resin compositions were obtained in the same manner as in Examples 1 to 4, 6 to 12 and Comparative Examples 1 to 5, except that a φ30 mm single screw extruder was used to produce the pellets. The kneading temperature of the thermoplastic resin composition was 230°C. When the mass proportion of the methacrylic resin (A) and the mass proportion of the thermoplastic polyurethane (B) in the thermoplastic resin compositions obtained in Examples 5 and 13 were analyzed, they were the same mass proportions as those shown in Table 2. The mass proportion of the tertiary amine in the thermoplastic resin compositions obtained in Examples 5 and 13 was 0 mass%, and the mass proportion of the tertiary amine in the thermoplastic polyurethane (B) was 0 mass%.

[0085] [Table 2]

[0086] <Plate sample> (injection molding) The obtained thermoplastic resin composition pellets were put into an injection molding machine and molded into a 100 mm square plate with a thickness of 2 mm to prepare a plate sample for evaluation. The mold used had its surface (mold cavity inner surface) polished with a polishing grit of 8000. The molding conditions for the evaluation plate samples were set as follows. Molding temperature (cylinder temperature): 220℃~250℃ Mold temperature: 65℃ Also, in order to enhance the transferability of the mold surface polished with a polishing grade of 8000, it is important to keep the mold temperature higher during injection molding. However, if the mold temperature is too high, the cooling time will be too long, making it impractical. The temperature range of the mold to improve their quality is 40°C or higher and 100°C or lower, more preferably 50°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. In this case, 65°C was selected from among them.

[0087] <ISO dumbbell test piece> (Injection molding) The pellets of the obtained thermoplastic resin composition were put into an injection molding machine to mold ISO No. 1 dumbbell test pieces, which were used as samples for evaluation. The molding conditions conformed to ISO K6717-2.

[0088] As shown in Table 3, in Examples 1 to 3, 6, 7, 10, 11, and 13, it was possible to produce a thermoplastic resin composition that had excellent transparency, scratch resistance, and toughness, and also showed good yellowing resistance and processing stability during heat processing. In Comparative Example 1, the injection moldability, processing stability, toughness, and scratch resistance were good, but since a thermoplastic polyurethane (B) having a monomer structure derived from a polyether was used as the monomer structure, the total light transmittance was low, the haze was high, and the transparency was not good. In addition, the yellowing resistance during heat processing was not good. In Comparative Example 2, the injection moldability, processing stability, toughness, and scratch resistance were good, but since a thermoplastic polyurethane (B) having a monomer structure derived from a non-alicyclic aliphatic isocyanate was used as the monomer structure, the total light transmittance was poor, the haze was high, and the transparency was not good. In addition, the yellowing resistance during heat processing was slightly inferior to Examples 1 to 3, 6, 7, 10, 11, and 13, although it was at a practically sufficient level. In Comparative Example 3, the injection moldability, yellowing resistance during heat processing, processing stability, and transparency were excellent, but the scratch resistance and toughness were not good. In Comparative Example 4, since the methacrylic resin (A) does not contain any other vinyl monomer unit other than maleic acid and maleic anhydride copolymerizable with the methacrylic acid ester monomer or maleic acid and / or maleic anhydride monomer unit as a structural unit of the methacrylic resin (A), the transparency, scratch resistance, and toughness were good, but the yellowing resistance during heat processing and processing stability were not good, and the injection moldability was slightly inferior to Examples 1 to 3, 6, 7, 10, 11, and 13, although it was at a practically sufficient level. In Comparative Example 5, since the methacrylic resin (A) contained a large amount of maleic anhydride monomer units, the transparency, scratch resistance, and toughness were good, but the yellowing resistance and processing stability during heat processing were not good, and the injection moldability was also at a practically sufficient level but slightly inferior to Examples 1 to 3, 6, 7, 10, 11, and 13. In Example 4, the yellowing resistance during heat processing was slightly inferior to Examples 1 to 3, 6, 7, 10, 11, and 13, although it was at a practically sufficient level. In Example 5, the transparency and yellowing resistance were slightly inferior to Examples 1 to 3, 6, 7, 9 to 11, and 13, although it was at a practically sufficient level.In Example 8, although the level was sufficient for practical use, yellowing during injection molding was large and silver was easily generated, and the injection moldability was slightly inferior, and the yellowing resistance and processing stability against heat processing were slightly inferior. In addition, although the transparency was sufficient for practical use, it was slightly inferior compared to Examples 1 to 3, 6, 7, 10, 11, and 13. In Example 9, although the level was sufficient for practical use, the yellowing resistance during heat processing was slightly inferior compared to Examples 1 to 3, 6, 7, 10, 11, and 13. In Example 12, although the level was sufficient for practical use, it was slightly inferior in injection moldability, yellowing resistance during heat processing, and processing stability compared to Examples 1 to 3, 6, 7, 10, 11, and 13.

[0089] [Table 3] [Industrial Applicability]

[0090] According to the thermoplastic resin composition of the present invention, a molded article having good transparency and excellent toughness and scratch resistance can be obtained, and therefore the composition has industrial applicability, for example, as roofing materials used in buildings, automobiles, trains, or buses, films for vinyl greenhouses, liquid crystal protective films, protective materials used in indoor and outdoor lighting, signs, and meters, vehicle interior and exterior components, vehicle lighting components, ship lighting components, battery protective covers, and the like.

Claims

1. The thermoplastic resin composition contains 60 to 95 mass% of a methacrylic resin (A) that is composed of 93.0 to 99.5 mass% of methyl methacrylate monomer units, 0.5 to 7.0 mass% of methyl acrylate and / or ethyl acrylate monomer units, and 0 to 4.0 mass% of maleic acid and / or maleic anhydride monomer units, and 5 to 40 mass% of a thermoplastic polyurethane (B) that has a structural unit derived from a polyester polyol and a structural unit derived from an isocyanate having an alicyclic ring.

2. The thermoplastic resin composition according to claim 1 , wherein the structural unit derived from an isocyanate having an alicyclic ring has one alicyclic ring.

3. The thermoplastic resin composition according to claim 1 or 2, wherein the weight average molecular weight of the methacrylic resin (A) measured by gel permeation column chromatography (GPC) is 50,000 to 250,000.

4. The thermoplastic resin composition according to claim 1 , wherein the methacrylic resin (A) has an amount of unsaturated double bond terminals of 0.01 mol % or less.

5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein the mass ratio of the structural unit derived from an isocyanate having one alicyclic ring is 70 mass% or more relative to 100 mass% of the total mass of the structural units derived from an isocyanate contained in the thermoplastic polyurethane (B).

6. A thermoplastic resin composition described in any one of claims 1 to 5, wherein the content of tertiary amine in 100 mass% of the thermoplastic resin composition is 0.9 mass% or less.

7. A thermoplastic resin composition described in any one of claims 1 to 6, wherein the total content of the methacrylic resin (A) and the thermoplastic polyurethane (B) is 80 mass% or more relative to 100 mass% of the thermoplastic resin composition, and which is used for molding.

8. A thermoplastic resin composition described in any one of claims 1 to 7, wherein a flat plate sample having a thickness of 2 mm obtained by injection molding at a molding temperature of 220 to 250°C and a mold temperature of 65°C and polishing the surface with a polishing grit of 8000 has a total light transmittance of 89% or more as measured in accordance with JIS K7361.

9. A method for producing the thermoplastic resin composition according to any one of claims 1 to 8, characterized in that the methacrylic resin (A) and the thermoplastic polyurethane (B) are blended at a temperature in the range of 200 to 260°C.

10. A molded article comprising the thermoplastic resin composition according to claim 1 .

11. An injection molded article comprising the thermoplastic resin composition according to any one of claims 1 to 8.

12. A method for producing an injection molded article, comprising molding the thermoplastic composition according to any one of claims 1 to 8 at a cylinder temperature of 200 to 260°C.

Citation Information

Patent Citations

  • Aqueous polyurethane acrylic emulsion composition, and an aqueous emulsion coating material obtained by using the same

    JP1998265735A

  • Acrylic overlay film

    JP2002356658A

  • Acrylic resin film and injection molded item with it laminated thereto

    JP2003183471A

  • Medical devices containing silicate and carbon particles

    JP2010537793A

  • Aqueous acrylic urethane resin composition and coating film formed by applying and drying the same

    JP2013035895A